Diferenciacija terminalnih traheid kasnega lesa pri navadni jelki v dormantnem obdobju - Gričar, Jožica (Les (Ljubljana), 2003)
The differentiation of terminal latewood tracheids of silver firs (Abies alba) was studied during dormant period. Samples of wood and cambium were taken from 10 apparently healthy mature trees in the middle of October, November and March. According to light microscopy and transmission electron microscopy, cambial cell-divisional activity was completed in all investigated trees in October, whereas process of differentiation was still ongoing in the youngest tracheids close to the cambium in trees with broader annual xylem growth rings. Cell wall formation and lignification of terminal latewood tracheids were completed in all trees in November. The cambial cell-divisional activity and also differentiation ended later in trees with broader annual xylem growth rings. However, differentiation of terminal latewood tracheids in all investigated trees was completed before winter.
Keywords: navadna jelka; traheide; celica; celična stena; diferenciacija; lignifikacija; mikroskopija